2017
DOI: 10.1037/aca0000078
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental control and Chinese middle school adolescents’ creativity: The mediating role of autonomous motivation.

Abstract: The present study attempted to examine the relationships between perceived parental control and Chinese middle school adolescents' creativity assessed in terms of ideational fluency, flexibility, and originality, as well as the mechanism underlying these associations from the Self-Determination Theory perspective. A total of 503 Chinese middle school students participated in this study, and their autonomous motivation, perceived parental control and creativity were measured. Results indicated that behavioral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 60 publications
7
34
0
1
Order By: Relevance
“…Children raised under excessive parental control may have limited creativity, whereas those raised through parenting practices that ensure a robust parent–child relationship and encourage self‐management may become more creative in adulthood. Studies along similar lines conducted in China have also indicated that moderate parental control can stimulate general creativity (Liu et al, ; Ren et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Children raised under excessive parental control may have limited creativity, whereas those raised through parenting practices that ensure a robust parent–child relationship and encourage self‐management may become more creative in adulthood. Studies along similar lines conducted in China have also indicated that moderate parental control can stimulate general creativity (Liu et al, ; Ren et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Perceived parental behavioral control is associated with lower levels of antisocial behaviour in China (Barber, Stolz, Olsen, Collins, & Burchinal, ). Empirical studies have shown that parental control is positively related to ideational fluency, flexibility and originality (Ren et al, ). Thus, the relationship between parenting and children's growth and creativity remains inconclusive.…”
Section: Related Theories and Proposed Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations